(untitled) (Marketing Journal, 2026)
Abstract This article examines the theoretical and practical aspects of implementing artificial intelligence (AI)-based marketing systems in the service sector of Uzbekistan. The purpose of the study was to identify the prospects for digital transformation of CRM systems and the application of AI technologies in service organizations. The research methodology included system analysis, comparative analysis, secondary statistical data analysis, and synthesis of scientific sources. The findings indicate that AI-based CRM systems play a significant role in predicting customer behavior, developing personalized marketing offers, and improving service quality. The conclusion provides scientific and practical recommendations for the phased implementation of AI-driven CRM systems in service sector enterprises. Keywords: CRM marketing, artificial intelligence, service sector, digital transformation, customer loyalty, marketing automation, Big data analytics, customer experience, personalization, predictive analytics, chatbot technologies, omnichannel marketing, customer segmentation, loyalty Programs, conversion Rate, digital Platforms, real-Time Marketing.